2013
DOI: 10.1186/1471-244x-13-187
|View full text |Cite
|
Sign up to set email alerts
|

Altered cardiac autonomic nervous function in depression

Abstract: BackgroundDepression is an independent risk factor for coronary artery disease. Autonomic instability may play a mediating or moderating role in this relationship; however this is not well understood. The objective of this study was to explore cardiac autonomic function and cardiac arrhythmia in depression, the correlation between depression severity and Heart Rate Variability (HRV) related indices, and the prevalence of arrhythmia.MethodsIndividuals (n = 53) with major depression as assessed by the Diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 32 publications
(31 reference statements)
8
63
3
Order By: Relevance
“…Since that report, evidence has accumulated supporting a connection between low HRV and cardiovascular morbidity and mortality (Hillebrand et al, 2013;Stapelberg et al, 2012;Taylor, 2010;Thayer and Lane, 2007). Low HRV has also been recognised as an important covariate of major depressive disorder (Kemp et al, 2012;Wang et al, 2013) and is hypothesised to underlie the link between depression and cardiovascular events (Huikuri and Stein, 2012;Stapelberg et al, 2012;Taylor, 2010). diabetes, smoking, high cholesterol, insufficient exercise) are linked to low HRV.…”
Section: The Importance Of Autonomic Regulationmentioning
confidence: 99%
“…Since that report, evidence has accumulated supporting a connection between low HRV and cardiovascular morbidity and mortality (Hillebrand et al, 2013;Stapelberg et al, 2012;Taylor, 2010;Thayer and Lane, 2007). Low HRV has also been recognised as an important covariate of major depressive disorder (Kemp et al, 2012;Wang et al, 2013) and is hypothesised to underlie the link between depression and cardiovascular events (Huikuri and Stein, 2012;Stapelberg et al, 2012;Taylor, 2010). diabetes, smoking, high cholesterol, insufficient exercise) are linked to low HRV.…”
Section: The Importance Of Autonomic Regulationmentioning
confidence: 99%
“…However, the effects of sympathetic and parasympathetic activities on the interaction between stress and depression of the autonomic nervous system remains were unclear [15]. HRV is an electrocardiograph-based technique developed to assess the relative influences of sympathetic and vagal branches over heart's beat-tobeat activity [16]. However, many factors that influence on depression have been associated with the decreased cardiac vagal control.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies [6], [7], [8] have shown highly related connections between psychiatric and cardiac disorders which suggests the potentiality of using cardiac indicators as supplementary tools in psychological condition evaluation. Studies on HRV in mental diseased patients have provided evidences for the possible connection between autonomic nerves system and mental disorders [12], [14], [15], [16]. However, there are some limitations using HRV analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Increased mortality of cardiac disorders raises attention to the links between autonomic dysfunction and psychiatric disorders. A body of research implicates a relative reduction in cardiac vagal tone, and reduced heart rate variability (HRV) in psychiatric disorder [12], [13], [14], [15], [16]. Photoplethysmography (PPG), signal reflecting the arterial blood pressure variability, has shown to be a simple noninvasive tool for cardiac autonomic nervous system assessment.…”
Section: Introductionmentioning
confidence: 99%